Evaluation of the Effects of Urbanization on Carbon Emissions: The Transformative Role of Government Effectiveness - Chen, Fuzhong; Liu, Aiwen; Lu, Xiuli; Zhe, Ru; Tong, Jiachen; Akram, Rabia (Frontiers in Energy Research, 2022)
With the rapid economic growth and urbanization, the environment is continuously degrading, and the problem of global warming caused by increasing carbon emissions has been highly highlighted. Utilizing panel data of the Organization for Economic Cooperation and Development (OECD) countries from 1996 to 2018, this study aims to evaluate the effects of urbanization on carbon emissions and explore the transformative role of government effectiveness. To produce more accurate estimates, the approach of the feasible generalized least squares is employed, and the heteroskedastic and correlated errors are considered due to the significant differences among the OECD countries. The results suggest an inverted U-shaped nexus between urbanization and carbon emissions, and for most OECD countries, the enhancement of urbanization is positive to increase carbon emissions. Besides, urbanization positively contributes to government effectiveness. As a transformator, government effectiveness negatively contributes to the effects of urbanization on increasing carbon emissions. That is, with the advancement of government effectiveness, the positive role of urbanization in emitting more carbon dioxide will be transformed to help the OECD countries mitigate carbon emissions. Hence, the findings are informative for policymakers to take effective measures to accelerate the process of urbanization and formulate active measures to improve government effectiveness, thereby decreasing carbon emissions and further mitigating global warming.